1999
DOI: 10.1086/315027
|View full text |Cite
|
Sign up to set email alerts
|

Proteases fromAspergillus fumigatusInduce Interleukin (IL)–6 and IL‐8 Production in Airway Epithelial Cell Lines by Transcriptional Mechanisms

Abstract: Proteases secreted by Aspergillus fumigatus induce the production of cytokines by epithelial cells, including interleukin (IL)-6 and IL-8. In the present study, we focused on the mechanism(s) by which A. fumigatus-derived proteases elicit cytokine production in epithelial cells. In the epithelial cell line A549, IL-6 and IL-8 mRNA levels were enhanced by proteases as a result of transcriptional induction of the respective genes. Transcriptional induction of both genes coincided with enhanced DNA binding of nuc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
96
2
2

Year Published

2007
2007
2013
2013

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 143 publications
(108 citation statements)
references
References 33 publications
8
96
2
2
Order By: Relevance
“…In the present study, we demonstrated that Pen c 13 induced IL-8 release from HAECs and that this effect was almost completely blocked by protease inhibitors. Extracts of dust mite and fungi have been shown to directly induce airway inflammation, characterized by IL-8 and IL-6 expression in the airway epithelium (7)(8)(9)(10). Although the precise role of Pen c 13 in allergic disease is unclear, fungal proteases have been linked to allergic asthma, and many of the Ags frequently implicated in disease are proteases.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In the present study, we demonstrated that Pen c 13 induced IL-8 release from HAECs and that this effect was almost completely blocked by protease inhibitors. Extracts of dust mite and fungi have been shown to directly induce airway inflammation, characterized by IL-8 and IL-6 expression in the airway epithelium (7)(8)(9)(10). Although the precise role of Pen c 13 in allergic disease is unclear, fungal proteases have been linked to allergic asthma, and many of the Ags frequently implicated in disease are proteases.…”
Section: Discussionmentioning
confidence: 99%
“…M any aeroallergens have been shown to possess proteolytic activity; this is the case for house dust mite (Dermatophagoides pteronyssinus), which contains the serine proteases, Der p 3 and Der p 9, and the cysteine protease, Der p 1 (1-3), cockroach extracts (4 -6), and house fungal extracts (Alternaria alternata, Cladosporium herbarum, and Aspergillus fumigatus) (7)(8)(9). Allergens with protease activities may be involved in the pathogenesis of asthma by proteolytic attack and direct activation of epithelial cells.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Secretion of cytokines from the airway epithelium contributes to the inflammation response. Cell stimulation assays show that increased cytokine secretion can be induced by both endogenous proteases from the coagulation cascade and inflammatory cells (Schoenmakers et al, 2005;Wang et al, 2006), as well as exogenous proteases derived from mites (King et al, 1998;Tomee et al, 1998), molds (Borger et al, 1999;Kauffmann et al, 2000), bacteria (Lourbakos et al, 2001;Ubl et al, 2002;Kida et al, 2007;, cockroaches (Bhat et al, 2003), and fish (Larsen et al, 2008). In addition to their well known role in digestion of dietary proteins, blood coagulation, and homeostasis, recent studies have revealed a novel role of serine proteases as signalling molecules acting via protease-activated receptors (PARs) in innate and adaptive immunity (Shpacovitch et al, 2008).…”
Section: Introductionmentioning
confidence: 99%